Kontribusi Penguasaan Semantik terhadap Kemampuan Membaca Pemahaman Mahasiswa IIPK Universitas Negeri Padang - Afnita . (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2012)
This study aims to determine the contribution of semantic mastery to the ability of the Archives, Library and Information Science (IIPK) students in comprehending the reading texts. The result of this study indicates that the semantic mastery has a positive and significant relationship (with a coefficient of determination of 0.524). This means that the reading comprehension of IIPK students of UNP is 25.4% determined by mastery of semantics, and the remaining 74.6% is determined by other factors. Keywords: semantic mastery, reading comprehension, contribution